2008
DOI: 10.1039/b714882h
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of quantitative methods for monitoring dermal and inhalation exposure to propiconazole

Abstract: Quantitative methods to measure dermal and inhalation exposure to the fungicide propiconazole were developed in the laboratory and applied in the occupational exposure setting for monitoring five farm workers' exposure during pesticide preparation and application to peach crops. Dermal exposure was measured with tape-strips applied to the skin, and the amount of propiconazole was normalized to keratin content in the tape-strip. Inhalation exposure was measured with an OVS tube placed in the worker's breathing-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 8 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…In this study, the GM of urinary glyphosate next morning after spraying day (μg/g creatinine) did not significantly differ from that at the end of spraying task. Connolly et al (2018) estimated half-life of glyphosate in urine was between 3 and 20 h after exposure; sampling times of less than 24 h would not allow sufficient time for pesticide absorption and excretion, particularly when skin is the dominant route of exposure (Flack et al 2008;Vitali et al 2009). The urinary glyphosate on the next morning was used for comparison among different spraying equipment.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the GM of urinary glyphosate next morning after spraying day (μg/g creatinine) did not significantly differ from that at the end of spraying task. Connolly et al (2018) estimated half-life of glyphosate in urine was between 3 and 20 h after exposure; sampling times of less than 24 h would not allow sufficient time for pesticide absorption and excretion, particularly when skin is the dominant route of exposure (Flack et al 2008;Vitali et al 2009). The urinary glyphosate on the next morning was used for comparison among different spraying equipment.…”
Section: Discussionmentioning
confidence: 99%
“…However, the LOD for penconazole-COOH is almost three orders of magnitude lower than the peak level seen in the volunteer study so if residents were exposed to penconazole, even at levels below the ADI, metabolites should be detectable in urine samples collected within 4 to 5 half-lives; the volunteer study showed levels at least 10× the LOD at 24 h post-dose. Furthermore, it is likely that if residents were exposed to penconazole it would be mostly through dermal exposure [ 20 ] rather than ingestion, with the delay in peak exposure as seen in the tebuconazole study [ 18 , 19 ]. In these scenarios, collecting urine samples the following day would increase the likelihood of detection in samples collected the following day.…”
Section: Discussionmentioning
confidence: 99%
“…External exposure was assessed collecting information on the use of PEN and investigating dermal exposure. In fact, dermal exposure was recognized as the main exposure route both during pesticide mixing, loading and application, and during re-entry activities Flack et al, 2008). PEN metabolites were measured in urine sampled before, during and after the application/re-entry in the treated vineyards.…”
Section: Introductionmentioning
confidence: 99%